DEVELOPMENT OF TOURISM VILLAGES AND STRENGTHENING The Role of Tourism Awareness Groups Based on Heptahelix of Millennials Of Agrotourism Model: New Ideas For The Development Of Pandemic-Era Tourism Villages - Anna Gustina Zainal; Dian Kagungan; Yulia Neta; Rudy Rudy; Helvi Yanfika (LP2M STP Mataram, 2022)
The purpose of this community service activity is to encourage the acceleration of tourism village development and increase the institutional ability of tourism awareness groups through training and assistance in order to develop the superior potential of agro-tourism-based tourism